Impact of Gender-Based Violence on Community Development: Case Study of Rumonge Commune (Burundi) - Ndabarushimana, Alexis; Mfisumukiza, Gilbert (European Scientific Journal, ESJ, 2022)
Gender-based violence (GBV) is a global problem that affects women and girls of all races, colors, and creeds. It occurs across all socioeconomic and cultural backgrounds, and in many societies, including Burundi despite different international, regional, and national instruments ratified to protect women against GBV and its effects. This study conducted with 96 individuals selected using Alain Bouchard’s technic highlights the impact of gender-based violence (GBV) on community development and provides some suggestions for action in remedy to gender-based violence persistence for community development. It specifically shows the reasons behind the persistence of gender-based violence in Rumonge Commune and its implications on the bad living conditions of families. To achieve this, we opted for qualitative approaches with the use of the interview guide and quantitative with the use of a questionnaire administered directly to heads of households distributed in 6 zones of Rumonge Commune. The study found that the reasons behind the persistence of GBV in Rumonge are fundamentally linked to Burundian culture and tradition that structure how people have to behave and live in society. In view of the impact of GBV, identified as a constraint to individual and societal development, this article highlights a set of activities to be done to reduce GBV. These include community dialogues around laws regarding families and development; education and awareness of the impacts and ways to prevent it for community development. Perpetrators must also be properly prosecuted and victims provided with all the needed resources for treatment and judicial processes.